MOTIVASI DAN EKSPEKTASI PARA PEMBURU BEASISWA KULIAH KE LUAR NEGERI - Restu Andrian; Teuku Azhari; Nur Akmaliyah; Ika Kana Trisnawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Studying abroad is no longer the dream of a handful of Indonesian students. There are a variety of accesses enabling Indonesian students to realize their goals, one of which is the opportunity for external funding or scholarships. The scholarship is a support for the students who excel, but are constrained by economic problems to live abroad. This study aimed to identify the motivation of tertiary education graduates in Aceh, in participating in the scholarships to study abroad, and the expectations they wished to achieve from these scholarships. This study was a case study, using a questionnaire in data collection. A sample of 100 people were selected randomly. The data were then analyzed with the SPSS to see descriptive statistics and the significance of the data sets